Breivik’s Long Shadow?: the Impact of the July 22, 2011 Attacks on the Modus Operandi of Extreme-right Lone Actor Terrorists - Macklin, Graham (Perspectives on terrorism, 2021)
This article investigates the extent to which Norwegian terrorist Anders Behring Breivik has influenced the modus operandi of extreme right lone actor terrorists in the decade since his own attacks on July 22, 2011. The article presents an overview of the principal cases in which Breivik’s name has appeared as either a potential influence or inspiration. It argues that despite his own best efforts, detailed in his manifesto, and the Christchurch shootings on March 15, 2019—for which his inspiration, at first glance, appears to be writ large—Breivik’s actual tactical influence upon the subsequent trajectory of extreme attacks from the extreme right has been limited.